2012
DOI: 10.4012/dmj.2011-203
|View full text |Cite
|
Sign up to set email alerts
|

<I>In vitro</I> effect of hesperidin on root dentin collagen and de/re-mineralization

Abstract: The aims of this study were to investigate the effects of hesperidin, a citrus flavonoid, on human root dentin demineralization and collagen preservation, and compare it with chlorhexidine and grape seed extract. Specimens were assigned to different treatment groups: hesperidin, chlorhexidine and grape seed extract. Specimens were subjected to pH cycling by demineralization for 14 h, incubation in testing solutions for 2 h and remineralization in presence of bacterial-derived collagenase for 8 h, for 8 days. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 31 publications
2
35
0
4
Order By: Relevance
“…G. chinensis remineralization is believed to be mediated through different polyphenol compounds that act as Ca 2+ ion carriers into the lesion body [Cheng et al, 2015]. Hesperidin, a citrus flavonoid, and gum arabic, an Acacia exudate, are other natural products that have been found to suppress aciddependent demineralization and boost remineralization even under fluoride-free conditions [Islam et al, 2012;Onishi et al, 2008].…”
Section: Fluoride Boostersmentioning
confidence: 99%
“…G. chinensis remineralization is believed to be mediated through different polyphenol compounds that act as Ca 2+ ion carriers into the lesion body [Cheng et al, 2015]. Hesperidin, a citrus flavonoid, and gum arabic, an Acacia exudate, are other natural products that have been found to suppress aciddependent demineralization and boost remineralization even under fluoride-free conditions [Islam et al, 2012;Onishi et al, 2008].…”
Section: Fluoride Boostersmentioning
confidence: 99%
“…It has also been reported that hesperidin reduced the susceptibility of dentine lesions to acid-dependent demineralization with the potential to promote the remineralization process [Hiraishi et al, 2011]. In another paper, hes- peridin was found to reduce lesion depth and mineral loss, indicating that hesperidin inhibited demineralization and probably enhanced remineralization even under fluoride-free conditions [Islam et al, 2012]. The mechanism of hesperidin may be related to its interaction with collagen and/or noncollagenous proteins, resulting in stabilizing the collagen matrix and induction of remineralization [Liu et al, 2004].…”
Section: Hesperidinmentioning
confidence: 92%
“…A number of natural flavonoids, such as GSE and hesperidin (HPN), have been used on root caries to study their cross-linking effects on demineralized lesions in order to render collagen matrix more stable 18. Flavonoids are polyphenolic compounds in plant-derived food products.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, HPN affects bone formation 18,20. Islam et al applied HPN to tooth structures in an in vitro caries model and concluded that its cross-linking properties might inhibit degradation of collagen and demineralization of bovine root dentin 18…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation